(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Non-alcoholic fatty liver disease (NAFLD) - common chronic liver disease, characterized by pathological accumulation of fat droplets, not associated with alcohol. NAFLD is often a component of other diseases such as metabolic syndrome, diabetes, obesity, and contributes to the prevalence of among the population. In the early stages of NAFLD, specific treatment is ineffective and the disease progresses due to nonspecific clinical signs.